Analysis of Social Conflicts in Poland’s Soundscape as a Challenge to Socio-Acoustics - BERNAT, Sebastian (Archives of Acoustics, 2016)
The study objective was to understand the character and location of social conflicts in Poland’s soundscape. The analyses were based on a review of press and Internet articles from the years 2008–2015 and reports on noise, preceded by a review of the legal framework of protection against noise in Poland. Questionnaire surveys concerning Poland’s national parks and health resorts and the city of Lublin were an additional source of information. In the case of the former, the surveys were supplemented with a general examination of the acoustic determinants of social conflicts in the Podzamcze district.An analysis shows that sound in landscape has been a source of more than 100 social conflicts which were most frequently related to unpleasant sounds (noise nuisance) and the right to peace and quiet. The public demands acoustic comfort, one of the determinants of the quality of life. Therefore, it is necessary to know the public opinion on soundscapes (survey of sound preferences). Public consultations concerning the assessment of acoustic disturbance and sound preferences will make it possible to avoid social conflicts arising from insufficient knowledge. A major role is also played by the education of the public and decision-makers through sound awareness campaigns, e.g. as part of ecology education. The subjective assessment of noise nuisance severity and the acoustic design of public spaces should be an integral part of environmental noise control programmes and revitalisation programmes.The conducted studies demonstrated that understanding the character and location of social conflicts in soundscape is a major scientific problem. Its resolution requires combining sociological studies (questionnaire for the valuation of the subjective feelings of respondents) with field analyses (observations, acoustic measurements). It is a promising research field that has been developed to a limited extent so far.